Upbringing In Modern Single-Parent Families - Shaamirova Yulduzkhan Kabildjanovna (Genius Journals, 2023)
This article describes modern single-parent familes Approaches to problems, conflicts and their solutions in these familes are given.
Keywords: Broken heart; negative thoughts; life’s blessings